Islam and Democracy: In Search of a Viable Synthesis - Effendy, Bahtiar (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 1995)
Democracy is actually a concept that is understood and practiced heterogeneous. However, there are basic elements or